2017
DOI: 10.1515/biolog-2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, diversity and some ecological characteristics of ostracods (Crustacea: Ostracoda) in Gökçeada (Imbros) Island (Northern Aegean Sea, Turkey)

Abstract: The aim of this study was to determine the environmental factors affecting distribution and diversity of ostracods (Crustacea: Ostracoda) in the inland waters of the northern Aegean Sea island of Gökçeada (Imbros), Turkey. Over a period of one year, sampling of ostracods was performed in order to estimate the composition, richness, and diversity of the ostracod assemblages from the Gökçeada Island. A total of 18 ostracod species were identified from 28 sampling sites during the course of the study. In both win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The ostracod assemblages at the Enez lagoon complex were mainly represented by C. torosa (70.5%; dominant in seven lagoons), followed by L. elliptica (9.44%). Studies by Altınsaçlı (2004Altınsaçlı ( , 2014 and Perçin-Paçal et al (2017) indicated that individual numbers of C. torosa are always higher than L. elliptica, as was also the case in the present study.…”
Section: Analysis Of the Dominant Ostracod Species Cyprideis Torosa Asupporting
confidence: 85%
See 1 more Smart Citation
“…The ostracod assemblages at the Enez lagoon complex were mainly represented by C. torosa (70.5%; dominant in seven lagoons), followed by L. elliptica (9.44%). Studies by Altınsaçlı (2004Altınsaçlı ( , 2014 and Perçin-Paçal et al (2017) indicated that individual numbers of C. torosa are always higher than L. elliptica, as was also the case in the present study.…”
Section: Analysis Of the Dominant Ostracod Species Cyprideis Torosa Asupporting
confidence: 85%
“…Loxoconcha elliptica has frequently been found in salinity ranges between 18 and 30 psu typical of shallow coastal brackish water habitats such as lagoons, river mouths, and salt marshes (Altınsaçlı 2004;Athersuch et al 1989;Besonen 1997;Bonaduce et al 1975;Mischke et al 2012;Pascual & Carbonel 1992). This typical lagoonal species has previously been determined in lagoons in Turkey (Altınsaçlı 2004;Altınsaçlı 2014;Perçin-Paçal 2017). As well as Loxoconcha elliptica being able to tolerate high salinity (up to 65 psu) like C. torosa (Zaninetti 1982;.…”
Section: Analysis Of the Dominant Ostracod Species Cyprideis Torosa Amentioning
confidence: 92%
“…Until now, there have been five published studies (Gülen 1985;Kılıç et al 2000;Altınsaçlı and Griffiths 2002;Rasouli et al 2014;Perçin-Paçal et al 2017) and one unpublished Previous studies have documented a total of 28 non-marine ostracod species. Nine of which were also found in the present study (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In some valleys of Gökçeada, there are many freshwater streams, and these water resources are rich in animal and plant species. Human impact on nature is great, and this is expected to cause a loss of habitat (Perçin Paçal et al, 2017). The Büyükdere creek in Kaleköy (35T0405784; 4453706), where the specimens were caught, is at sea level and has summer houses and agricultural areas around it.…”
Section: Study Sites and Sample Collectionsmentioning
confidence: 99%